Phytogenics in Ginger, Origanum vulgare, and Syzygium aromaticum and Their Potential as a Feed Additive against Clostridium perfringens in Broiler Production - Valdez, Gilmour; Shyur, Lie-Fen; Wang, Sheng-Yang; Chen, Shuen-Ei (Animals (Basel), 2023)
Necrotic enteritis is a devastating disease in chickens mainly caused by Clostridium perfringens—particularly, Net-B toxin-producing strains. In order to combat necrotic enteritis in broiler production, natural growth promoters, as well as anti-inflammatory and non-antibiotic remedies, were developed for anti-microbial resistance due to its status as a global pandemic. Herein, phytogenic ginger, wild marjoram, and cloves were reviewed as potential alternatives to antibiotics for their anti-microbial functions. These phytogenics contain active ingredients that efficiently modulate the immune response and improve intestinal morphology and overall growth performance, even under stress and infection conditions. Most of the beneficial effects can be attributed to their anti-inflammatory functions, primarily the inhibition of the NF-κB and MAPK pathways. Phytogenics and their active ingredients represent potential substitutes for antibiotic growth promoters, further serving as anti-microbial remedies in the treatment of birds with infections.